AXL is a predictor of poor survival and of resistance to anti-EGFR therapy in RAS wild-type metastatic colorectal cancer. (October 2020) - Cardone, Claudia; Blauensteiner, Bernadette; Moreno-Viedma, Veronica; Martini, Giulia; Simeon, Vittorio; Vitiello, Pietro P.; Ciardiello, Davide; Belli, Valentina; Matrone, Nunzia; Troiani, Teresa; Morgillo, Floriana; Zito Marino, Federica; et al.
Abstract: Background: RAS mutations are the only validated biomarkers in metastatic colorectal cancer (mCRC) for anti-epidermal growth factor receptor (EGFR) therapy. Limited clinical information is available on AXL expression, marker of epithelial to mesenchymal transition, in mCRC. Methods: AXL was retrospectively assessed by immunohistochemistry in 307 patients. RAS wild-type (WT) patients ( N = 136) received first-line anti-EGFR–based therapy; RAS mutant patients ( N = 171) received anti-angiogenic–based regimens. Preclinical experiments were performed using human RAS WT CRC cell lines and xenograft models. AXL RNA levels were assessed in a cohort of patients with available samples at baseline and at progression to anti-EGFR treatment and in the GSE5851 dataset. Results: AXL was expressed in 55/307 tumour tissues, correlating with worse survival in the overall population (AXL-positive, 23.7 months; AXL-negative, 30.8 months; HR, 1.455, P = 0.032) and in RAS WT patients (AXL-positive, 23.0 months; AXL-negative, 35.8 months; HR, 1.780, P = 0.032). Progression-free survival (PFS) in the RAS WT cohort was shorter in the AXL-positive cohort (6.2 months versus 12.1 months; HR, 1.796, P = 0.013). Three-dimensional cultures obtained from a patient following anti-EGFR therapy resulted AXL-positive, showing resistance to anti-EGFR drugs and sensitivity to AXL inhibition. AXL transfection in CRC cell lines induced AXL overexpression and resistance to the EGFR blockade. At progression to cetuximab, 2/10 SW48-tumour xenograft mice showed AXL expression. Consistently, AXL RNA levels increased in 5/7 patients following anti-EGFR therapy. Moreover, in the GSE5851 dataset higher AXL RNA levels correlated with worse PFS with cetuximab in KRAS-exon2 WT chemorefractory patients. Conclusions: AXL is a marker of poor prognosis in mCRC with consistent clinical and preclinical evidences of involvement in primary and acquired resistance to anti-EGFR drugs in RAS WT patients. Highlights: AXL, marker of epithelial to mesenchymal transition, is expressed in metastatic colorectal cancer (mCRC). AXL is associated with poor prognosis and shorter progression-free survival in patients with RAS wild-type (WT) mCRC. AXL is a biomarker of both primary and acquired resistance to anti-epidermal growth factor receptor therapies in RAS WT mCRC.